Histopathological analysis of placentas with congenital cytomegalovirus infection. (January 2019) - Uenaka, Mizuki; Morizane, Mayumi; Tanimura, Kenji; Deguchi, Masashi; Kanzawa, Maki; Itoh, Tomoo; Yamada, Hideto
Abstract: Introduction: Cytomegalovirus (CMV) infection is the most common cause of congenital viral infections in humans. The unusual structure of the placenta plays a pivotal role in CMV transmission from mothers to fetuses. The aim of this study was to evaluate the histopathological findings of placentas with congenital CMV infections. Methods: We obtained placental specimens from 35 women who had newborns with congenital CMV infections. Placental specimens, extraplacental membranes, and umbilical cords were stained with hematoxylin and eosin, and subjected to immunohistochemical analysis. We evaluated the localization of CMV-infected cells and other histological parameters. Results: Thirty (86%) of the 35 placentas tested positive for CMV-infected cell proteins by immunohistochemistry. A majority of CMV-positive cells were present in fibroblasts and endothelial cells in the villi. The number of CMV-infected cells was inversely correlated to gestational age at delivery. The frequency of chronic villitis (65% vs. 11%; p < 0.01) and changes of the villi (38% vs. 0%; p < 0.05) in the placentas from mothers with symptomatic congenital CMV infections was higher than those observed in samples from mothers with asymptomatic congenital infections. The frequency of changes of the decidua (43% vs. 5%; p < 0.01) in the placentas from mothers with non-primary CMV infections was higher than those from mothers with primary infections. Discussion: Chronic villitis and changes of the villi were associated with symptomatic congenital CMV infections. The changes of the decidua were associated with congenital CMV infections, in mothers with non-primary CMV infections. Highlights: CMV-infected placentas show histopathological changes and reduce placental functions. The number of CMV-infected cells was inversely correlated to gestational age. Villitis and changes of the villi were related to symptomatic CMV infection. Deciduitis was related to maternal non-primary CMV infection.